Assessment of maximal handgrip strength: how many attempts are needed?. Issue 3 (2nd February 2017) - Reijnierse, Esmee M.; de Jong, Nynke; Trappenburg, Marijke C.; Blauw, Gerard Jan; Butler‐Browne, Gillian; Gapeyeva, Helena; Hogrel, Jean‐Yves; McPhee, Jamie S.; Narici, Marco V.; Sipilä, Sarianna; Stenroth, Lauri; van Lummel, Rob C.; et al.
Abstract: Background: Handgrip strength (HGS) is used to identify individuals with low muscle strength (dynapenia). The influence of the number of attempts on maximal HGS is not yet known and may differ depending on age and health status. This study aimed to assess how many attempts of HGS are required to obtain maximal HGS. Methods: Three cohorts (939 individuals) differing in age and health status were included. HGS was assessed three times and explored as continuous and dichotomous variable. Paired t ‐test, intraclass correlation coefficients (ICC) and Bland–Altman analysis were used to test reproducibility of HGS. The number of individuals with misclassified dynapenia at attempts 1 and 2 with respect to attempt 3 were assessed. Results: Results showed the same pattern in all three cohorts. Maximal HGS at attempts 1 and 2 was higher than at attempt 3 on population level ( P < 0.001 for all three cohorts). ICC values between all attempts were above 0.8, indicating moderate to high reproducibility. Bland–Altman analysis showed that 41.0 to 58.9% of individuals had the highest HGS at attempt 2 and 12.4 to 37.2% at attempt 3. The percentage of individuals with a maximal HGS above the gender‐specific cut‐off value at attempt 3 compared with attempts 1 and 2 ranged from 0 to 50.0%, with a higher percentage of misclassification in middle‐aged and older populations. Conclusions: Maximal HGS is dependent on the number of attempts, independent of age and health status. To assess maximal HGS, at least three attempts are needed if HGS is considered to be a continuous variable. If HGS is considered as a discrete variable to assess dynapenia, two attempts are sufficient to assess dynapenia in younger populations. Misclassification should be taken into account in middle‐aged and older populations.